CHARACTERIZATION OF LOCAL CATTLE HUSBANDRY PRACTICES IN HADIYA ZONE, SOUTHERN REGION OF ETHIOPIA - LOMBEBO, WONDIMU AYELE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study was conducted to characterize cattle husbandry practices in Hadiya zone, southern Ethiopia. Three districts were purposively selected. A total of 180 households were selected randomly. Six focus group discussions with key informants were held. There were significant (p<0.05) differences across the districts in livestock number per households. Cattle are the dominant livestock species, mainly used for milk and draught power. The mean cattle holding per household were 10.87±1.16, 6.8±.40 and 15.22±1.70 in Shashogo, Misha and Soro districts respectively. The most popular farming system in the areas was mixed crop-livestock production. Local female and male cattle reached sexual maturity in 49.0 and 44.7 months in Shashogo, 52.7 and 48.8 months in Misha, and 50.1 and 46.8 months in Soro districts, respectively. Local female cattle in the research area had an average age at first calving of 53.2 months in Shashogo, 59.1 months in Misha, and 54.3 months in Soro districts. In the districts, natural mating was the most common and common method of mating. Cattle production was hampered by a lack of feed and water, illnesses, repeated draughts, infrastructure, and other factors such as land scarcity, poor capital, and a lack of agricultural extension.